Pentingnya Penguasaan Bahasa Mandarin bagi Lulusan STT Kerusso dalam Misi Penginjilan Global - Joshua Christian; Edward Nimits Abraham; Eunike Eunike; Lucky Antonio; Matius Kala'tiku (Sekolah Tinggi Teologia Kerusso Indonesia, 2019)
This research focuses on the importance of Mandarin language proficiency for active students of Sekolah Tinggi Teologi (STT) Kerusso in the context of global evangelism missions. The urgency of this study lies in the growing role of foreign languages, particularly Mandarin, in reaching unreached communities across different parts of the world. With a large number of Mandarin speakers worldwide, proficiency in this language is essential for those involved in evangelism missions to establish effective communication and expand the mission's reach. The primary objective of this research is to demonstrate the importance of foreign language proficiency, especially Mandarin, for active STT Kerusso students involved in global evangelism missions. This study aims to provide insights for theological education institutions in designing curricula that better support foreign language acquisition as an integral part of mission preparation. This research employs a qualitative method with an approach that includes in-depth interviews, literature review, and participatory observation. Interviews were conducted with active students and alumni of STT Kerusso who have been involved in evangelism missions in Mandarin-speaking communities. The collected data were analyzed descriptively to identify key themes related to the role of foreign languages in evangelism. The findings of this study are expected to provide a deeper understanding of the urgency of foreign language proficiency in global evangelism missions and offer strategic recommendations for STT Kerusso in preparing its students to face future challenges in evangelism.